Clinical Features and Risk Factors of Autoimmune Liver Involvement in Pediatric Inflammatory Bowel Disease. Issue 2 (August 2016) - Bramuzzo, Matteo; Martelossi, Stefano; Torre, Giuliano; Cardile, Sabrina; Arrigo, Serena; Vignola, Silvia; Ferrari, Federica; Zuin, Giovanna; Illiceto, Maria Teresa; Gasparetto, Marco; Pellegrino, Salvatore; Romano, Claudio; et al.
ABSTRACT: Objectives: Autoimmune liver disease is reported in up to 7.8% of children with inflammatory bowel disease. A distinct inflammatory bowel disease phenotype has been suggested in adults and in small pediatric cohorts. The aim of the study was to evaluate the features of inflammatory bowel disease associated with autoimmune liver diseases and to analyze the characteristics of the liver disease. Methods: Information on patients was obtained from the Italian Pediatric Inflammatory Bowel Disease Registry. Data of patients with and without autoimmune liver disease were compared. Results: Autoimmune liver disease was detected in 6.8% of the 677 patients enrolled and was significantly associated with the diagnosis of ulcerative colitis (83%), with pancolonic involvement (84%), and with perinuclear antineutrophil cytoplasmic antibody positivity (41%) (all P s  < 0.05). Autoimmune liver disease was defined as sclerosing cholangitis in 61% of the patients and as an overlap syndrome in 33%. Concomitant intra- and extrahepatic biliary involvement was reported in 61% of cases, whereas exclusive extrahepatic lesions were reported in 21%. Hepatobiliary complications were observed in 9% of the patients during follow-up. Conclusions: Autoimmune liver disease, especially sclerosing cholangitis, was significantly more common in patients with extensive ulcerative colitis. Although complications are relatively rare in the pediatric age, monitoring is recommended.